Comparison of Judges' Decisions on Isbat Nikah in the Marriage of Minors in the Religious Courts of Bulukumba - Tarimana, Sitti Fatimah; Rahmi; Mahmusin, Muhammad Arash bin (Parewa Saraq: Journal of Islamic Law and Fatwa Review, 2023)
Isbat nikah (isbat of marriage) is needed by some people who do not have a marriage book, because with the approval of the Judge's decision, the party applying for isbat can register their marriage book. This study aims to reveal the judge's consideration in deciding the isbat nikah case of marriage of minors at the Bulukumba Religious Court. This empirical research was conducted at the Bulukumba Religious Court. The research approach is juridical-normative by observing the decision. Data collection techniques in this study are interviews, observation and documentation. The results of the study indicate that the Judge's consideration in deciding the Isbat Nikah Case for Marriage of Minors remains based on Law Number 1 of 1974 on the amendment of Law Number 16 of 2019. Whatever the reason for the litigant in applying for Isbat Nikah when violating the existing law, the judge has the right to decide the case accordingly. The causes of child marriage in Bulukumba Regency are caused by a number of factors, including economy, education and socio-culture. Socio-cultural factors are more often used as a reason by perpetrators of early marriage, with following in the footsteps of parents as the most frequently mentioned factor. An understanding of the changes in the age of marriage rules in Indonesia must be socialised so that there are no violations of the marriage law.